High Rate of Obesity-Associated Hypertension among Primary Schoolchildren in Sudan - Zeena Salman; Gregory D. Kirk; Mark D. DeBoer (International Journal of Hypertension)
Cardiovascular disease (CVD) frequently has roots in childhood, including following childhood-onset hypertension. Incidence of CVD has increased in developing countries in East Africa during recent urbanization. Effects of these shifts on childhood hypertension are unclear. Our objectives were to (1) Determine the prevalence of hypertension among primary schoolchildren in Khartoum, Sudan; (2) Determine whether hypertension in this setting is associated with obesity. We performed a cross sectional study of 6-12y children from two schools randomly selected in Khartoum, Sudan. Height, weight, BMI, BP and family history of hypertension were assessed. Age-, height- and gender-specific BP curves were used to determine pre-hypertension (90–95%) and hypertension (>95%). Of 304 children, 45 (14.8%) were overweight; 32 (10.5%) were obese; 15 (4.9%) were pre-hypertensive and 15 (4.9%) were hypertensive. Obesity but not family history of hypertension was associated with current hypertension. In multiple logistic regression, adjusting for family history, children who were obese had a relative-risk of 14.7 (CI 2.45-88.2) for systolic hypertension compared to normal-weight children. We conclude that overweight and obesity are highly prevalent among primary schoolchildren in urban Sudan and are strongly associated with hypertension. That obesity-associated cardiovascular sequelae exist in the developing world at young ages may be a harbinger of future CVD in sub-Saharan Africa.